The Comparative Study of the Crime Rate of Theft Before and During the Pandemic in Barangay Citrus City of San Jose Del Monte Bulacan: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The crime of theft was lawfully defined as the removal of the personal belongings of another without the latter's consent. In the criminological classification of crimes, theft was classified as an acquisitive crime because when a person commits the crime of theft, they will acquire or gain something. Before the pandemic in 2018, the most prevalent crime here in the Philippines was theft, which increased crime against properties by up to 30 percent of the country’s crime list. According to costs abroad, the City of San Jose Del Monte, Bulacan, is considered one of the most dangerous places to live in or travel in, and according to this data, the crime rate of theft is approximately 24.01 percent. This study will determine our local chief executives' basic remedies, rules, and regulations to solve this problem. Every year, there is an increasing number of crimes here in the Philippines, mostly thefts. This crime was classified under crimes against property in the revised penal code. This study focuses on one barangay where the crime of theft was prevalent. We chose this topic because we want to know what this pandemic's roles are in reducing theft crime in this barangay. This study will provide information on the theft crime rate before the pandemic and the theft crime rate during the pandemic. The researchers aim to compare the crime rate of theft before and during the pandemic in Barangay Citrus City of San Jose Del Monte Bulacan. In this study, the researchers used mixed qualitative and quantitative approaches to verify their observations regarding the crime rate of theft before and during the pandemic. The researcher would utilize a descriptive research method in the study. After conducting the research method using the self-made questionnaire, the researcher gathered sufficient data to make the study possible and accurate. Moreover, analytical tools like Input, Process and Output were used to accomplish the study's effectiveness. The study concluded that based on the demographic profile of the two groups of respondents, the Barangay Officials and community at Barangay Citrus, the majority of the respondents came from the age bracket 18-25 years old, female, married, and college level.  Based on the result of the study, Curfew hours and Patrol affect the crime rate of theft before and during the pandemic. Strictly implementing curfew hours and patrol lessen the crime rate of theft during the pandemic. Individual negligence, poverty, drugs related, and unemployment were the factors affecting the crime rate of theft both before and during the pandemic in Barangay Citrus City of San Jose Del Monte Bulacan.